(untitled) (Journal of Scientific Research, 2024)
In order to improve our knowledge of cation-anion interactions in ionic liquids, we optimized the 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMImBF4]), and their interactions with CO2, with a focus on structural properties and vibrational behavior relevant to chemical applications such as carbon capture. By using density functional theory (DFT), the structures of the cation, anions, and cation-anion ion pairs of [EMImBF4] with CO2 were optimized. Vibrational spectroscopy was employed to emphasize structural properties, and vibrational frequencies of EMImBF4 and EMImBF4-CO2 (monomer) compounds were calculated. The scaled values were compared to experimental far-infrared and far-infrared Raman spectra to validate the theoretical findings.The study identified the most stable geometries of [EMImBF4] and [EMImBF4]-CO2 interactions, showing specific vibrational modes upon interaction with CO2 that align well with experimental data. These insights highlight the potential of [EMImBF4] in gas separation and capture, demonstrating its unique physicochemical properties and reinforcing the importance of understanding IL-CO2 interactions for developing efficient carbon capture technologies.